SISTEM PEMANTAU LOKASI BURUNG MERPATI BALAP BERBASIS IoT (INTERNET of THINGS) - Ramadhan, Bagaskara (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2020)
Abstract The purpose of this research is to discuss and create amonitoring system on IoT-based racing pigeons so that they cansee the location of racing pigeons and minimize the factors thatcause racing pigeons. This research was conducted using themethod designed, system design, subsystem design, hardwaredesign, software design, hardware and software design, andtesting analysis. The results showed that the location monitoringdevice on the racing pigeon that could provide information on thelocation of the racing pigeon obtained an average difference inerror distance around 2.853 meters with an average time to sendthe racing pigeon location information for 10 seconds.